The Catholic Church in Polish History - Ramet, Sabrina P. author. aut Link
XXIX, 300 p. 7 illus. in color.
Keywords: The book chronicles the evolution of the church's political power throughout Poland's unique history. Beginning in the tenth century, the study first details how Catholicism overcame early challenges in Poland, from converting the early polytheists to pushing back the Protestant Reformation half a millennium later. It continues into the dawn of the modern age—including the division of Poland between Prussia, Russia, and Austria between 1772 and 1795, the interwar years, the National Socialist occupation of World War Two, and the communist and post-war communist eras—during which The Church only half-correctly presented itself as a steadfast protector of Poles, with clergy members who either stood up to foreign authorities or collaborated with those same Nazi and Communist leaders. This study ends with a consideration of how the Church has taken advantage of the fall of communism to push its own social agenda, at times against the wishes of most Poles.